Xanthogranulomatous pyelonephritis caused by an unusual pathogen Raoultella ornithinolytica: a case report - Atalay Kutlu; Akif Erbin; Turan Ozdemir; Ahmet Eren Sagir; Begum Calim Gurbuz; Halil Lutfi Canat (Folia Medica)
Xanthogranulomatous pyelonephritis (XGP) is a rare and severe chronic inflammatory condition of the kidney. XGP’s exact etiology remains unclear, although it is frequently associated with chronic urinary obstruction and infections within the urinary tract. Superinfections such as Escherichia coli, Proteus mirabilis, and occasionally Pseudomonas species typically cause XGP. Documented cases of Raoultella ornithinolytica (R. ornithinolytica) infections in humans, particularly within the urinary tract, are limited. However, advancements in diagnostic techniques are expected to increase the detection of such rare pathogens. To the best of our knowledge, currently, there is no evidence in the literature indicating that this pathogen is responsible for XGP. We present a case of XGP in which we isolated R. ornithinolytica and discuss its treatment in the current literature.